An 8-Year-Old Child with Delayed Diagnosis of Netherton Syndrome - Alexander K. C. Leung; Benjamin Barankin; Kin Fon Leong (Hindawi Limited, 2018)
We report an 8-year-old boy with Netherton syndrome who was misdiagnosed and treated as severe atopic dermatitis. The diagnosis of Netherton syndrome was not made until the child was 8 years of age. We discuss the pitfalls in the diagnosis and alert physicians to the proper and early diagnosis of this syndrome. The child was treated with a low dose (0.25 mg/kg) of oral acitretin and a topical moisturizer with marked improvement of his skin and pruritus in 2 months. At 6-month follow-up, the skin was almost clear of erythema and scaling, and the hair was longer and stronger. The dose of acitretin was reduced to 0.12 mg/kg for another 6 months and then discontinued.